Entre a verdade da ciência e a ciência da verdade: [re]pensando a recepção heideggeriana da noção moderna de ciência - Schessof, Gabriel (Universidade do Vale do Rio dos Sinos, 2024)
The present dissertation aims to discuss and explore the relationship between science and the notion of truth, with the main reference being the thought of the german philosopher Martin Heidegger (1889-1976). We work with the hypothesis that modern sciences do not have as part of their methodological horizon a concern with explaining and even understanding what it means when we say that something (normally a judgment) is true. Although we easily conceive that the scientific methodology developed since modernity is capable of grounding the truth of propositions or judgments, this same methodology does not include a moment of reflection and discussion aimed at fixing the conceptual sense of the notion of truth. In light of this problem, the research is divided into three parts. In the first, we aim to sustain that some reflections on the relationship between philosophy and science, considering two main objectives: i) we intend to argue that Heidegger's thought presents a position that is not essentially positive, but also not strictly hostile to the sciences, as is commonly interpreted; and ii) we intend to demonstrate how philosophical reflection on fundamental concepts (Grundbegriffe) implies and appears in the methodology of the sciences (regarding its origin, its results, limits, and presuppositions), despite their autonomy and independence from philosophy, particularly sparked in the mid XIX century. In the second part, we aim to sustain that the traditional philosophical notion of truth as adaequatio (adequacy or agreement between judgments and objects) is the prominent notion in scientific discourse. We will do this by presenting how Heidegger compreheend that the traditional notion of truth reaches its development in the history of philosophy and remains uncontested even in central modern philosophers for the subsequent methodological achievements of science, from which follows the common and insufficient conception of science as the totality established through an interconnection of true propositions. In the third and final part, we aim to elucidate and evaluate Heidegger's approach to the concept of agreement. We will show that this approach is primarily situated in Being and Time as the task of thinking the unconcealment as the originating phenomenon of truth. Here, philosophical inquiry into the sense of truth is linked to the endeavor of existential analytics of Dasein, precisely because the true, according to Heidegger's understanding, would be an implication of one of its modes of being (it would be an existential rather than a mere cognitive capacity). In summary, we seek the approximation and dialogue of this level of existential truth, which goes beyond the scope of the natural sciences, with the propositional – whose truth value can be grounded by them.
Keywords: Verdade; Ciência; Filosofia; Heidegger; Truth; Science; Philosophy; ACCNPQ::Ciências Humanas::Filosofia